Blossoms amid drought: a bibliometric mapping of research on drought stress in ornamental plants (1995–2025) - Karagüzel, Ümmü Özgül (Frontiers in Plant Science, 2025)
Drought stress is a major abiotic constraint limiting plant growth and ornamental quality. Despite the importance of ornamental species in global horticulture, they remain underrepresented in drought-related research compared to food and industrial crops. This study presents a bibliometric and network-based analysis of drought stress research in ornamentals from 1995 to 2025, based on 1,387 records from Web of Science and 1,212 from Scopus. After screening, 383 WoS and 436 Scopus records were retained, yielding 819 articles. Keyword analysis showed dominant themes in gas exchange, photosynthesis, stomatal conductance, proline, and antioxidant activity. Recent inclusion of transcription factors, RNA-seq, and proteomics suggests a growing molecular focus. Salt tolerance, evapotranspiration, and floral traits under drought were also highlighted. Microbial strategies, such as PGPR and mycorrhizae, appeared infrequently. China, the USA, and Spain were the leading contributors, supported by international collaborations. Core journals included HortScience, Scientia Horticulturae and Frontiers in Plant Science. This work outlines the field’s thematic structure and evolution, underscoring the need to integrate physiological, molecular, and ecological tools to strengthen drought resilience in ornamentals. This study conducts a longitudinal and network-based bibliometric analysis of drought stress research in ornamental plants, drawing from peer-reviewed literature published between 1995 and 2025 across the Web of Science Core Collection and Scopus databases.